A Patient With CAD Deficiency Responsive to Uridine and Literature Review - Zhou, Ling; Xu, Han; Wang, Tianshuang; Wu, Ye (Frontiers in Neurology, 2020)
CAD encodes a multifunctional enzyme involved in de novo pyrimidine biosynthesis, and pyrimidine can be alternatively recycled from uridine. Trio whole-exome sequencing identified CAD compound heterozygous mutations in a new male patient with global developmental delay (DD), refractory epilepsy, and anaemia with anisopoikilocytosis. We further reviewed all published cases with CAD deficiency. Five patients were collected from two publications, including three males and two females, and all presented with DD, drug-resistant epilepsy, and anaemia with anisopoikilocytosis. Four out of six patients (including the present case) were supplemented with uridine, which led to immediate cessation of seizures, resolved anaemia with anisopoikilocytosis, and progress in global development. The other two patients, who were not treated with uridine, died at the ages of four and five years. In summary, CAD deficiency is probably a treatable neurometabolic disorder.